2020
DOI: 10.24875/bmhim.20000174
|View full text |Cite
|
Sign up to set email alerts
|

Survival in pediatric patients with cancer during the COVID-19 pandemic: scoping systematic review

Abstract: Background: Coronavirus disease (COVID)-19 has currently affected 8,015,502 million people worldwide with global mortality around 5%. Information in pediatric cancer patients is still limited, but it is emerging day by day. The objective of this scoping review was to analyze the available data associated with COVID-19 infection and mortality in pediatric cancer patients and to provide useful information to plan and design strategies in this group. Methods: A search was conducted, and eight articles were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
2
10
0
2
Order By: Relevance
“…Previous reviews have not provided a systematic understanding of the associations of paediatric comorbidities and severe outcomes in children. Systematic reviews which were undertaken early in the pandemic highlighted some of the challenges around identifying comorbidities which were associated with severe disease, including pooled reporting of even common conditions such as asthma( 28) and a focus on individual comorbidities without a comparator group (29). Our nding that children with trisomy 21 were at increased risk of critical care admission and death has not been described before, although it is consistent with previous adult data (30).…”
Section: Discussionsupporting
confidence: 83%
“…Previous reviews have not provided a systematic understanding of the associations of paediatric comorbidities and severe outcomes in children. Systematic reviews which were undertaken early in the pandemic highlighted some of the challenges around identifying comorbidities which were associated with severe disease, including pooled reporting of even common conditions such as asthma( 28) and a focus on individual comorbidities without a comparator group (29). Our nding that children with trisomy 21 were at increased risk of critical care admission and death has not been described before, although it is consistent with previous adult data (30).…”
Section: Discussionsupporting
confidence: 83%
“…The systematic scoping review published by Dorantes‐Acosta et al. (June 2020) focused on survival in pediatric oncology patients during the COVID‐19 pandemic and included five studies also collated in our review, a 100% survival was reported 46 . Most cases in this review were reported in patients with leukemia, and fever was the commonest symptom in children requiring admission.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews have not provided a systematic understanding of the associations of paediatric comorbidities and severe outcomes in children. Systematic reviews which were undertaken early in the pandemic highlighted some of the challenges around identifying comorbidities which were associated with severe disease, including pooled reporting of even common conditions such as asthma(28) and a focus on individual comorbidities without a comparator group(29). Our finding that children with trisomy 21 were at increased risk of critical care admission and death has not been described before, although it is consistent with previous adult data(30).…”
Section: Discussionmentioning
confidence: 99%